2009
DOI: 10.2514/1.41252
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain Impedance Boundary Conditions for Simulations of Outdoor Sound Propagation

Abstract: Finite difference time-domain methods are well suited to study sound propagation in the context of transportation noise. In this paper, time-domain boundary conditions are considered for impedance models classically used for outdoor grounds. These impedance models have usually been obtained in the frequency domain and cannot be translated directly into the time domain. The derivation of the time-domain boundary condition is based on the approximation of the impedance as a sum of well-chosen template functions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…Its implementation has been described in detail in Cotté et al [2] and will be summarized in Sec. II.B.…”
Section: A Linearized Euler Equations Solvermentioning
confidence: 99%
See 4 more Smart Citations
“…Its implementation has been described in detail in Cotté et al [2] and will be summarized in Sec. II.B.…”
Section: A Linearized Euler Equations Solvermentioning
confidence: 99%
“…Following the original work of Tam and Auriault [8] and other works done in the community of duct acoustics to model the impedance of lining materials in the time domain [4,[9][10][11], others developed timedomain boundary conditions (TDBCs) from classical ground impedance models, such as the phenomenological Zwikker and Kosten model [12,13]. This former approach was used by Cotté et al [2], who proposed a TDBC for outdoor sound propagation based on a recursive convolution method originally developed in the context of electromagnetic propagation [14] and introduced in acoustics by Reymen et al [11]. It was shown that this TDBC is accurate and computationally efficient [15].…”
Section: Doi: 102514/1j050636mentioning
confidence: 99%
See 3 more Smart Citations